PENGARUH MODEL PEMBELAJARAAN KOOPERATIF TIPE JIGSAWTERHADAP HASIL BELAJAR SISWA SMANEGERI 1 PONTIANAK - Andreas Novianto; Sulistyarini Sulistyarini; Ludovicus Maditya Hari Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to determine effect of Jigsaw type cooperative learning models on learning outcomes in learning geography in class XI IPS Senior High School 1 Pontianak. The Research Method is an experimental method in the form of a Quasi Experimental Design Research with a Nonquivalent Control Group Design. The research population was all students of class XI IPS Senior High School 1 Pontianak with a sample of 64 students. The sampling technique is purposive sampling. Research instruments in the form of a final test in the form of multiple choice questions amounted to 40. The final test calculation results obtained an average of 85.400 experimental class and an average of 79.735 control class with a tcount of 4.172 and a table of 1.999. Through on tcount> ttable, means Ha is rejected then,there is differences in student learning outcomes in geography learning that applies the Jigsaw cooperative model with those that apply the group discussion learning method in class XI IPS Senior High School 1 Pontianak. Based on the results of the calculation of the effect size obtained d value of 0.934. This proves that the Jigsaw type cooperative model has a high influence on student learning outcomes in class XI IPS of Senior High School 1 Pontianak.Keyword: Cooperatif Jigsaw Model, Learning Outcomes